Can Bottom-Up Institutional Reform Improve Service Delivery? - Ezequiel Molina (Inter-American Development Bank (IDB), 2014)
This article makes three contributions to the literature. First, it provides new evidence of the impact of community monitoring interventions using a unique dataset from the Citizen Visible Audit (CVA) program in Colombia. In particular, this article studies the effect of social audits on citizens' assessment of service delivery performance. The second contribution is the introduction a theoretical framework to understand the pathway of change, the necessary building blocks that are needed for social audits to be effective. Using this framework, the third contribution of this article is answering the following questions: i) under what conditions do citizens decide to monitor government activity and ii) under what conditions do governments facilitate citizen engagement and become more accountable.
hdl:11319/6671
Keywords: H40; H83; 330; Economic development; Political economy; Social audit; Bottom up; Citizen participation; Corruption